Diagnóstico situacional sobre disposición final del aceite lubricante usado en centros automotrices y lubricadoras de la ciudad de Machala, 2022 - Castillo Cofre, Nicol Lissbeth; Cordova Camacho, Alex Fernando (Machala : Universidad Técnica de Machala, 2022)
Lubricating oil is an essential substance for motor vehicles to carry out their work correctly. Among its functions is to clean, lubricate and prevent corrosion and overheating of the engine. The daily use of the means of transportation places this product in high demand, and consequently the change of lubricating oil is a job that is carried out daily in the lubricators and automotive centers. This type of service generates considerable amounts of hazardous waste, and the establishments where these activities are carried out become contamination diffusion areas, for this reason the INEN 2266 Standard categorizes used lubricating oil as hazardous waste. The main objective of this research is to analyze the current state of the management and final disposal of used lubricating oils generated by the automotive centers and lubricators of the city of Machala in order to propose alternatives for the correct management and safe final disposal and so on. contribute to the care and protection of the environment.
El aceite lubricante es una sustancia esencial para que los automotores realicen de manera correcta su trabajo. Entre sus funciones está limpiar, lubricar y evitar la corrosión y calentamiento del motor. El uso diario de los medios de transporte pone en alta demanda este producto, y por consecuencia el cambio de aceite lubricante es un trabajo que se realiza diariamente en las lubricadoras y centros automotrices. Este tipo servicios genera cantidades considerables de residuos peligrosos, y los establecimientos donde se llevan a cabo estas actividades se convierten en áreas de difusión de contaminación, por esta razón la Norma INEN 2266 lo categoriza al aceite lubricante usado como residuo peligroso. La presente investigación tiene como objetivo principal, analizar el estado actual del manejo y disposición final de los aceites lubricantes usados generados por los centros automotrices y lubricadoras de la ciudad de Machala con la finalidad de proponer alternativas para el correcto manejo y disposición final segura y así contribuir al cuidado y protección del medio ambiente.
Keywords: ACEITE LUBRICANTE RESIDUAL; NORMA INEN 2266; RESIDUO PELIGROSO; PLAN DE GESTION INTEGRAL